(untitled) (ENTHYMEMA, 2025)
In this paper, the Author examines the theoretical and philosophical function of the recourse to myth in Elias Canetti’s works, with particular reference to his masterpiece as an essayist, Crowds and Power, and his Aufzeichnungen. In the first section, the Author outlines the main features of Canetti’s rediscovery of myth and mentions its textual sources. In the second section, the Author explores the connection between myth and the concept of metamorphosis, pivotal within Canetti’s philosophical anthropology. In the third section, the Author focuses on Canetti’s recourse to myth as an antidote to the shortcomings that characterize philosophy. In the fourth and final section, the Author takes into account the political potential inherent in myth. In opposition to a knowledge compromised with power, Canetti perceives his reliance on myth as a means to bring to light the point of view of the oppressed, the forgotten, the colonized.